Combination anesthetic therapy: co-delivery of ropivacaine and meloxicam using transcriptional transactivator peptide modified nanostructured lipid carriers in vitro and in vivo - Shu Yuan; Jun Chen; Shuo Feng; Min Li; Yingui Sun; Yuzhen Liu (Taylor & Francis Group, 2022)
Combination therapy combining two drugs in one modified drug delivery system is used to achieve synergistic analgesic effect, and bring effective control of pain management, especially postoperative pain management. In the present study, a combination of drug delivery technologies was utilized. Transcriptional transactivator (TAT) peptide modified, transdermal nanocarriers were designed to co-deliver ropivacaine (RVC) and meloxicam (MLX) and anticipated to achieve longer analgesic effect and lower side effect. TAT modified nanostructured lipid carriers (TAT-NLCs) were used to co-deliver RVC and MLX. RVC and MLX co-loaded TAT-NLCs (TAT-NLCs-RVC/MLX) were evaluated through in vitro skin permeation and in vivo treatment studies. NLCs-RVC/MLX showed uniform and spherical morphology, with a size of 133.4 ± 4.6 nm and a zeta potential of 20.6 ± 1.8 mV. The results illustrated the anesthetic pain relief ability of the present constructed system was significantly improved by the TAT modification through the enhanced skin permeation efficiency and the co-delivery of MLX along with RVC that improved pain management by reducing inflammation at the injured area. This study provides an efficient and facile method for preparing TAT-NLCs-RVC/MLX as a promising system to achieve synergistic analgesic effect.